Android-Based Application for Children’s Growth Monitoring as a Complement for Child Development Card - Pramuditha Shinta Dewi Puspitasari; Bety Etikasari; Trismayanti Dwi Puspitasari; Ria Chandra Kartika; Lukie Perdanasari; Arvita Agus Kurniasari (Jurusan Teknik Elektromedik, POLTEKKES KEMENKES Surabaya, Indonesia, 2022)
Posyandu is a community activity center to provide health services and family planning. Routine monthly weighing for toddlers is one of the activities carried out by the Posyandu. This activity aims to detect early childhood growth disorders to address these problems quickly and precisely. However, since the Covid-19 pandemic, the toddler Posyandu, held regularly every month, has been temporarily suspended until the pandemic ends. This situation causes monitoring of toddlers' growth, and development cannot be done. Therefore we need a mechanism for monitoring child growth and development that can be done online via a smartphone. In previous research has implemented several desktop, web, and mobile-based information systems, but they do not yet have complex features such as maternal and child health information management. The purpose of this research is to create an android-based application in the form of an information system for Child Development Posyandu, which will contain several features such as immunization schedules, monitoring of child growth and development, health news. This application development uses the design sprint method. The test results with the User Acceptance Test method of this android application to user respondents show that 80% of the applications are in a Good category and can be used at Posyandu.